Pengaruh Karakteristik Chief Executive Officer Terhadap Real Earnings Management Dengan Koneksi Politik Sebagai Moderasi - Ivone, Ivone; Vivin, Vivin; Karina, Ria (Universitas Gorontalo, 2024)
This study examined the relationship between CEO characteristics and real earnings management as a dependent variable and included political connections as a moderating variable for non-financial companies listed on the BEI (Indonesian Stock Exchange). The number of observation data sampled in this research was 1,546 data through a purposive sampling. The method applied in analyzing research data is using panel regression analysis and tested using Eviews10. Based on the results of this research, political connections have a significant positive effect on CEO tenure and real earnings management, however political connections cannot be proved to influence other variables in this study, including CEO ownership, CEO expertise, and CEO narcissism.